Water-based acrylate pressure-sensitive adhesive for battery label and preparation method of water-based acrylate pressure-sensitive adhesive

By optimizing the formulation and process of aqueous acrylate pressure-sensitive adhesive, the problems of poor bonding strength and edge curling in battery label materials are solved, and high-performance and environmentally friendly bonding effect is achieved to ensure the stability and aesthetics of the label.

CN119264844AActive Publication Date: 2025-01-07TAICHANG RESIN FOSHAN
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411660669.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-01-07
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The application of water-based pressure-sensitive adhesive in battery label materials has problems with poor bonding strength and edge-curling, which affects the stability and aesthetics of the label.

Method used

By optimizing the formulation of aqueous acrylate pressure-sensitive adhesive, select specific soft monomers, hard monomers, crosslinked monomers, emulsifiers and tackifiers, adjust their component ratios and process parameters to form a synergistic multi-level structure Design to improve bonding performance and curling resistance.

Benefits of technology

It significantly improves the bonding strength and anti-curlability of battery labels, ensuring that the labels are not easy to fall off or curl during long-term use, and provides a high-performance, environmentally friendly adhesive solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and particularly relates to a water-based acrylate pressure-sensitive adhesive for a battery label and a preparation method of the water-based acrylate pressure-sensitive adhesive. The water-based acrylate pressure-sensitive adhesive for the battery label is prepared from the following raw materials: a monomer, an initiator, an emulsifier, a tackifier, a chain transfer agent, a solvent, a buffering agent and a pH regulator. According to the water-based acrylate pressure-sensitive adhesive for the battery label provided by the invention, by optimizing a formula and a polymerization process, the viscosity of the water-based acrylate pressure-sensitive adhesive is remarkably improved, and firm bonding between the label and a battery shell is ensured; meanwhile, the pressure-sensitive adhesive shows excellent bonding strength, a stable bonding effect can be kept, and the label is effectively prevented from falling off; besides, due to the excellent anti-warping performance, it is ensured that the edge of the label is not prone to warping in the long-term use process, and therefore the overall durability and attractiveness of the battery label are improved, and a high-performance, environment-friendly and economical label adhesive solution is provided for battery manufacturers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and in particular relates to a water-based acrylic pressure-sensitive adhesive for a battery label and a preparation method thereof. Background Art

[0002] With the enhancement of global environmental awareness and the popularization of the concept of sustainable development, all walks of life have increasingly stringent requirements for the selection and use of materials, especially in the electronics, communications, automobile and other industries, the application of environmentally friendly materials has become an irreversible trend. In this context, water-based glue has gradually occupied an important position in various adhesive markets due to its low volatile organic compound (VOCs) emissions, environmental friendliness, easy processing and recycling.

[0003] However, although water-based glue has shown great application potential in many fields, its application in battery label materials faces some challenges. In particular, water-based pressure-sensitive adhesives, although they have environmental advantages, often have problems such as poor bonding strength and edge warping in actual applications. Poor bonding strength means that the label is easy to fall off or lose its stickiness after use, affecting the identification and tracking of the battery; and the edge warping problem may cause the edge of the label to lift up, which not only affects the appearance, but also may reduce the protection effect and readability of the label.

[0004] In response to the above problems, this study is dedicated to developing a water-based acrylic pressure-sensitive adhesive specifically for battery label materials. This pressure-sensitive adhesive aims to combine the environmental characteristics of water-based glue and the excellent performance of acrylic materials, and through innovative formula design and preparation process, it can achieve the improvement of bonding strength and effectively solve the warping problem. Summary of the invention

[0005] The purpose of the present invention is to provide a water-based acrylic pressure-sensitive adhesive for a battery label and a preparation method thereof. The water-based acrylic pressure-sensitive adhesive for a battery label not only meets the green environmental protection requirements, but also meets the stability and reliability requirements of the battery label in long-term use, and provides a high-performance and sustainable solution for battery manufacturers, promotes the greening and environmental protection process of battery label materials, and helps achieve sustainable development goals.

[0006] A water-based acrylic pressure-sensitive adhesive for a battery label, the preparation raw materials of which include monomers, initiators, emulsifiers, tackifiers, chain transfer agents, solvents, buffers, and pH regulators.

[0007] Preferably, the monomers include soft monomers, hard monomers, and cross-linking monomers.

[0008] Preferably, the soft monomer includes one or more of butyl acrylate, n-octyl acrylate, and isooctyl acrylate; further preferably, it is butyl acrylate.

[0009] Preferably, the hard monomer includes one or more of styrene, methyl methacrylate, and vinyl acetate; more preferably, styrene.

[0010] Preferably, the crosslinking monomer includes one or more of acrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, N-hydroxymethyl acrylamide, and glycidyl methacrylate; further preferably, acrylic acid and hydroxyethyl methacrylate.

[0011] Preferably, the mass ratio of acrylic acid to hydroxyethyl methacrylate is 1:(2-4); more preferably, it is 1:3.

[0012] Preferably, the mass ratio of the soft monomer, the hard monomer and the cross-linking monomer is (45-50):(1-3):1; more preferably, it is 95:4:2.

[0013] The inventors found that by selecting specific soft monomers, hard monomers, and cross-linking monomers, and adjusting the proportions of each component, it is possible to improve the adhesive performance of the pressure-sensitive adhesive while improving its resistance to warping. This is because there is a synergistic effect between these monomers. Butyl acrylate provides good initial adhesion and lasting adhesion, while styrene enhances the rigidity and cohesion of the glue, and the combination of the two achieves a balance between flexibility and rigidity. The three-dimensional network structure formed by the cross-linking reaction of acrylic acid and hydroxyethyl methacrylate further enhances the cohesion and mechanical strength of the glue, and improves its heat resistance and chemical resistance. This multi-level structural design enables the glue to have sufficient rigidity and cohesion while maintaining good flexibility, reducing the warping phenomenon. In addition, the presence of the cross-linked structure effectively prevents the degradation of the polymer during long-term use and extends the service life of the glue. Therefore, by adjusting the proportions of these monomers, synergy can be achieved in many aspects, significantly improving the comprehensive performance of the pressure-sensitive adhesive to meet the needs of applications such as battery labels.

[0014] Preferably, the initiator is one or both of ammonium persulfate and potassium persulfate; further preferably, it is ammonium persulfate.

[0015] Preferably, the added amount of the initiator is 0.3% to 0.5% of the monomer mass.

[0016] Preferably, the emulsifier includes a reactive emulsifier and an anionic emulsifier.

[0017] Preferably, the mass ratio of the reactive emulsifier to the anionic emulsifier is 1:(0.5-2); more preferably, it is 1:1.

[0018] Preferably, the reactive emulsifier is allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate and allyloxy nonylphenol propanol polyoxyethylene ether.

[0019] Preferably, the mass ratio of the allyloxy nonylphenol ether and its sulfonate to allyloxy nonylphenol propanol polyoxyethylene ether is (1-3):1; more preferably, it is 2:1.

[0020] Preferably, the effective content of the allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate is 95%, and the viscosity at 25° C. is less than 35,000 cps.

[0021] Preferably, the effective content of the allyloxy nonylphenol propanol polyoxyethylene ether is 99%, the viscosity at 25° C. is less than 300 cps, the acid value is 0.07-0.09 gKOH / g, the hydroxyl value is 73-75 mgKOH / g, and the HLB value is 12.6.

[0022] In some preferred embodiments, the allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate and allyloxy nonylphenol propanol polyoxyethylene ether are purchased from Guangzhou Shuangbang Trading Co., Ltd., DNS-86 and ANPEO10.

[0023] Preferably, the anionic emulsifier is sodium lauryl sulfate and alkylphenol polyoxyethylene ether.

[0024] Preferably, the mass ratio of sodium lauryl sulfate to alkylphenol polyoxyethylene ether is 1:(0.5-2); further preferably, it is 1:1.

[0025] Preferably, the alkylphenol polyoxyethylene ether has a cloud point of 68-78° C., a hydroxyl value of 87±5 mgKOH / g, and an HLB value of 13.3-14.

[0026] In some preferred embodiments, the alkylphenol polyoxyethylene ether is purchased from Hai'an Petrochemical Plant in Jiangsu Province, OP-10.

[0027] Preferably, the amount of the emulsifier added is 2% to 5% of the monomer mass.

[0028] The inventors found that by selecting a specific reactive emulsifier and anionic emulsifier as emulsifiers, the adhesive performance and anti-warping effect of the pressure-sensitive adhesive can be further improved. This may be because allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate and allyloxy nonylphenol propanol polyoxyethylene ether not only have the functions of traditional emulsifiers to reduce the surface tension of the system, promote monomer dispersion and stabilize the emulsion, but also can react chemically with the polymer chain, thereby more firmly anchored on the surface of the polymer particles. This chemical bonding reduces the migration and shedding of the emulsifier molecules, making the emulsion more stable, thereby improving the bonding strength and durability of the pressure-sensitive adhesive. In addition, the reactive emulsifier can also introduce additional cross-linking points in the polymer network, which helps to enhance the cohesion and anti-warping of the pressure-sensitive adhesive. Sodium lauryl sulfate and alkylphenol polyoxyethylene ether, as anionic emulsifiers, can work together with the reactive emulsifier to form more compact and uniform emulsion particles, thereby improving the microstructure and dispersion uniformity of the pressure-sensitive adhesive. The addition of anionic emulsifiers can also promote the interaction between polymer chains and form more physical crosslinking points. These crosslinking points help to improve the elastic modulus and deformation resistance of the pressure-sensitive adhesive, thereby further enhancing its anti-warping effect. In addition, anionic emulsifiers can also improve the wettability and permeability of the pressure-sensitive adhesive to the surface of the adherend, helping to form a more solid bonding interface. However, the use of an emulsifier alone may result in poor emulsion stability and affect the performance of the pressure-sensitive adhesive. At the same time, allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate has a strong polarity. Excessive use may cause the pressure-sensitive adhesive to decrease in wettability and affect the initial adhesion performance.

[0029] Preferably, the tackifier is one or more of an aqueous rosin tackifier emulsion and an aqueous terpene tackifier emulsion; further preferably, it is an aqueous rosin tackifier emulsion and an aqueous terpene tackifier emulsion.

[0030] Preferably, the mass ratio of the aqueous rosin tackifying emulsion to the aqueous terpene tackifying emulsion is (1-3):1; more preferably, it is 2:1.

[0031] Preferably, the aqueous rosin tackifying emulsion has a viscosity of 100-400 mPa·s at room temperature, a solid content of 55±2%, and a pH value of 6-8.

[0032] Preferably, the aqueous terpene thickening emulsion has a viscosity of 600-800 mPa·s at room temperature, a solid content of 60±2%, and a pH value of 6-8.

[0033] In some preferred embodiments, the aqueous rosin tackifying emulsion and the aqueous terpene tackifying emulsion are both purchased from Shenzhen Yoshida Chemical Co., Ltd., models 958 and 968.

[0034] Preferably, the amount of the tackifier added is 2% to 3% of the monomer mass.

[0035] The inventors found that by selecting specific aqueous rosin tackifying emulsion and aqueous terpene tackifying emulsion as tackifiers, the anti-warping effect of the pressure-sensitive adhesive can be further improved, and its solid content and viscosity can also be adjusted. This is because there is a significant synergistic effect between the two aqueous tackifying emulsions. The active functional groups in the rosin and terpene molecules can interact with each other to form a more complex and stable cross-linked network structure, which not only enhances the cohesion and adhesion of the pressure-sensitive adhesive, but also significantly improves its anti-warping effect and weather resistance. At the same time, the synergistic effect of the two tackifying emulsions can also effectively adjust the viscosity and solid content of the pressure-sensitive adhesive, so that the final product can meet the needs of different application occasions. In addition, this synergistic effect can also optimize the wettability and permeability of the pressure-sensitive adhesive, making it easier to form a good bonding interface with the surface of the adherend, thereby further improving the bonding effect.

[0036] Preferably, the chain transfer agent is n-dodecyl mercaptan.

[0037] Preferably, the added amount of the chain transfer agent is 0.05% to 0.1% of the monomer mass.

[0038] Preferably, the buffer is one or more of sodium bicarbonate, potassium carbonate, sodium carbonate, and ammonium bicarbonate; further preferably, it is sodium bicarbonate.

[0039] Preferably, the amount of the buffer added is 0.05% to 0.1% of the monomer mass.

[0040] Preferably, the pH adjuster is one or more of ammonia water, sodium hydroxide, ethanolamine, and ethylenediamine; more preferably, it is ammonia water.

[0041] Preferably, the solvent is deionized water.

[0042] Preferably, the amount of the solvent added is 55% to 60% of the monomer mass.

[0043] The method for preparing the water-based acrylic pressure-sensitive adhesive for battery labels comprises the following steps: S1. Mix and stir the emulsifier, monomer, chain transfer agent and deionized water for 1-2 hours to obtain liquid 1; S2, dividing the initiator into initiator 1 and initiator 2, and preparing an initiator 2 solution by mixing initiator 2 and deionized water; S3. The buffer is dissolved in deionized water to prepare a buffer solution. Stir until the buffer is dissolved, raise the temperature to 80-90°C, add initiator 1 and continue stirring until dissolved, and simultaneously drop liquid 1 and initiator 2 solution. The addition should be completed within 3-4 hours. Keep warm at 80-90°C for 1-2 hours, cool to 30-50°C, add viscosity enhancer, continue stirring for 15-30 minutes, add deionized water and pH adjuster to adjust the pH of the system to 6-7, continue stirring for 15-20 minutes, and filter to obtain.

[0044] In the process of preparing water-based acrylic pressure-sensitive adhesive, the monomer droplet acceleration, reaction temperature and water ratio are key factors affecting the performance of the pressure-sensitive adhesive. Too fast a droplet acceleration may lead to violent polymerization and monomer residue, affecting the stability of the pressure-sensitive adhesive and the performance of the final product; the temperature must be controlled within an appropriate range. Too high a temperature may easily cause gelation, while too low a temperature may cause the reaction rate to be too slow; the water ratio directly affects the moisture content of the pressure-sensitive adhesive. Too high a temperature may lead to stratification and precipitation, while too low a temperature may cause the coating to dry too quickly and crack. Therefore, strict control of these process parameters is the key to obtaining a water-based acrylic pressure-sensitive adhesive with excellent performance and stable quality.

[0045] Preferably, in step S1, the amount of deionized water added is 15% to 20% of the mass of the monomer.

[0046] Preferably, in step S2, the mass ratio of initiator 1 to initiator 2 is 1:(1-2); more preferably, it is 2:3.

[0047] Preferably, in step S2, the mass percentage of initiator 2 in the initiator 2 solution is 5% to 7%.

[0048] Preferably, in step S3, the mass percentage of the buffer in the buffer solution is 0.2% to 0.5%.

[0049] Compared with the prior art, the advantages and beneficial effects of the present invention are: 1. The present invention provides a water-based acrylic pressure-sensitive adhesive for a battery label. By optimizing the formula and polymerization process, the viscosity of the water-based acrylic pressure-sensitive adhesive is significantly improved, ensuring the firm bonding between the label and the battery shell; at the same time, the pressure-sensitive adhesive exhibits excellent bonding strength, can maintain a stable bonding effect, and effectively prevent the label from falling off; in addition, its excellent anti-warping performance ensures that the edge of the label is not easy to warp up during long-term use, thereby improving the overall durability and aesthetics of the battery label, and providing a high-performance, environmentally friendly and economical label adhesive solution for battery manufacturers.

[0050] 2. The present invention can improve the adhesive performance of the pressure-sensitive adhesive while improving its resistance to warping by selecting specific soft monomers, hard monomers, and cross-linking monomers and adjusting the proportions of each component.

[0051] 3. The present invention can further improve the adhesive performance and anti-warping effect of the pressure-sensitive adhesive by selecting a specific reactive emulsifier and anionic emulsifier as emulsifiers.

[0052] 4. The present invention can further improve the anti-warping effect of the pressure-sensitive adhesive and adjust its solid content and viscosity by selecting specific water-based rosin tackifying emulsion and water-based terpene tackifying emulsion as tackifiers.

[0053] 5. In the process of preparing the water-based acrylic pressure-sensitive adhesive, the product performance of the pressure-sensitive adhesive is adjusted by controlling the monomer droplet addition rate, reaction temperature and water ratio. DETAILED DESCRIPTION

[0054] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] The raw materials used in the present invention are all commercially available, specifically: Allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate, effective content is 95%, viscosity at 25°C is <35000cps; allyloxy nonylphenol propanol polyoxyethylene ether, effective content is 99%, viscosity at 25°C is <300cps, acid value is 0.07~0.09gKOH / g, hydroxyl value is 73~75mgKOH / g, HLB value is 12.6; both were purchased from Guangzhou Double Bond Trading Co., Ltd., DNS-86 and ANPEO10.

[0056] Alkylphenol polyoxyethylene ether, cloud point of 68~78℃, hydroxyl value of 87±5mgKOH / g, HLB value of 13.3~14, purchased from Hai'an Petrochemical Plant, Jiangsu Province, OP-10.

[0057] The viscosity of the aqueous rosin tackifying emulsion at room temperature is 100~400mPa·s, the solid content is 55±2%, and the pH value is 6~8; the viscosity of the aqueous terpene tackifying emulsion at room temperature is 600~800mPa·s, the solid content is 60±2%, and the pH value is 6~8; both were purchased from Shenzhen Yoshida Chemical Co., Ltd., models 958 and 968.

[0058] Example 1 The present embodiment provides a water-based acrylic pressure-sensitive adhesive for a battery label, wherein the raw materials for preparing the water-based acrylic pressure-sensitive adhesive are monomers, initiators, emulsifiers, tackifiers, chain transfer agents, solvents, buffers, and pH regulators.

[0059] The monomers are soft monomers, hard monomers and cross-linking monomers, and the mass ratio is 95:4:2.

[0060] The soft monomer is butyl acrylate.

[0061] The hard monomer is styrene.

[0062] The cross-linking monomers are acrylic acid and hydroxyethyl methacrylate, with a mass ratio of 1:3.

[0063] The initiator is ammonium persulfate, and the added amount is 0.4% of the monomer mass.

[0064] The emulsifiers are reactive emulsifiers and anionic emulsifiers, and the mass ratio is 1:1.

[0065] The reactive emulsifier is allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate and allyloxy nonylphenol propanol polyoxyethylene ether, with a mass ratio of 2:1.

[0066] The anionic emulsifier is sodium lauryl sulfate and alkylphenol polyoxyethylene ether, and the mass ratio is 1:1.

[0067] The amount of the emulsifier added is 4% of the monomer mass.

[0068] The tackifiers are water-based rosin tackifier emulsion and water-based terpene tackifier emulsion, with a mass ratio of 2:1.

[0069] The added amount of the tackifier is 2.5% of the monomer mass.

[0070] The chain transfer agent is n-dodecyl mercaptan, and the added amount is 0.08% of the monomer mass.

[0071] The buffer is sodium bicarbonate, and the added amount is 0.08% of the monomer mass.

[0072] The pH regulator is aqueous ammonia.

[0073] The solvent is deionized water.

[0074] The added amount of the solvent is 58% of the monomer mass.

[0075] The method for preparing the water-based acrylic pressure-sensitive adhesive for battery labels comprises the following steps: S1, mixing the emulsifier, monomer, chain transfer agent and deionized water for 1.5 hours to obtain liquid 1; S2, dividing the initiator into initiator 1 and initiator 2, and preparing an initiator 2 solution by mixing initiator 2 and deionized water; S3. The buffer is dissolved in deionized water to prepare a buffer solution. Stir until the buffer is dissolved, raise the temperature to 85°C, add initiator 1 and continue stirring until dissolved, and simultaneously drop liquid 1 and initiator 2 solution. The addition should be completed within 3.5 hours. Keep warm at 85°C for 1.5 hours, cool to 40°C, add viscosity enhancer, continue stirring for 20 minutes, add deionized water and pH adjuster to adjust the pH of the system to 6.5, continue stirring for 18 minutes, and filter to obtain.

[0076] In the step S1, the amount of deionized water added is 18% of the weight of the monomer.

[0077] In the step S2, the mass ratio of initiator 1 to initiator 2 is 2:3.

[0078] In the step S2, the mass percentage of initiator 2 in the initiator 2 solution is 6%.

[0079] In step S3, the mass percentage of the buffer in the buffer solution is 0.4%.

[0080] Example 2 The difference between this embodiment and embodiment 1 is that the monomers are soft monomers, hard monomers, and cross-linking monomers, and the mass ratio is 96:3:2.

[0081] Example 3 The difference between this embodiment and embodiment 1 is that the mass ratio of the reactive emulsifier to the anionic emulsifier is 2:3.

[0082] Comparative Example 1 The difference between this comparative example and Example 1 is that the monomers are soft monomers, hard monomers, and cross-linking monomers, and the mass ratio is 98:2:1.

[0083] Comparative Example 2 The difference between this comparative example and Example 1 is that the cross-linking monomer is acrylic acid.

[0084] Comparative Example 3 The difference between this comparative example and Example 1 is that the emulsifier is a reactive emulsifier.

[0085] Comparative Example 4 The difference between this comparative example and Example 1 is that the reactive emulsifier is allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate.

[0086] Comparative Example 5 The difference between this comparative example and Example 1 is that the tackifier is an aqueous rosin tackifier emulsion.

[0087] Comparative Example 6 The difference between this comparative example and Example 1 is that the added amount of the tackifier is 1% of the weight of the monomer.

[0088] Comparative Example 7 The difference between this comparative example and Example 1 is that the preparation method of the water-based acrylic pressure-sensitive adhesive for battery labels comprises the following steps: S1, mixing the emulsifier, monomer, chain transfer agent and deionized water for 1.5 hours to obtain liquid 1; S2, dividing the initiator into initiator 1 and initiator 2, and preparing an initiator 2 solution by mixing initiator 2 and deionized water; S3. The buffer is dissolved in deionized water to prepare a buffer solution. Stir until the buffer is dissolved, raise the temperature to 85°C, add initiator 1 and continue stirring until dissolved, and simultaneously drop liquid 1 and initiator 2 solution. The addition should be completed within 2 hours. Keep warm at 85°C for 1.5 hours, cool to 40°C, add viscosity enhancer, continue stirring for 20 minutes, add deionized water and pH adjuster to adjust the pH of the system to 6.5, continue stirring for 18 minutes, and filter to obtain.

[0089] Comparative Example 8 The difference between this comparative example and Example 1 is that the preparation method of the water-based acrylic pressure-sensitive adhesive for battery labels comprises the following steps: S1, mixing the emulsifier, monomer, chain transfer agent and deionized water for 1.5 hours to obtain liquid 1; S2, dividing the initiator into initiator 1 and initiator 2, and preparing an initiator 2 solution by mixing initiator 2 and deionized water; S3. The buffer is dissolved in deionized water to prepare a buffer solution. Stir until the buffer is dissolved, raise the temperature to 85°C, add initiator 1 and continue stirring until dissolved, and simultaneously add liquid 1 and initiator 2 solution dropwise. The addition should be completed within 3.5 hours. Keep warm at 100°C for 1.5 hours, cool to 40°C, add viscosity enhancer, continue stirring for 20 minutes, add deionized water and pH adjuster to adjust the pH of the system to 6.5, continue stirring for 18 minutes, and filter to obtain.

[0090] Performance Testing The initial adhesion was tested according to GB 4852-2002, with the ball number indicating the adhesion; the peeling force was tested according to GB / T 2792-1998; the lasting adhesion was tested according to GB / T 4851-1998, and the time for the ball to fall was recorded; the viscosity was tested according to GB / T 2794-1995, and the test was performed using a rotational viscometer at a constant temperature of 25°C; the pressure-sensitive adhesive was applied to the battery label, and then attached to the outside of the No. 5 battery, and observed whether it would curl after 7 days. The results are shown in Table 1.

[0091] Table 1 Test results According to statistics, the water-based acrylic pressure-sensitive adhesive for battery labels prepared in Examples 1 to 3 of the present invention has good initial adhesion, high peeling force, excellent sticking performance, and a certain viscosity, and will not warp when used for battery labels. In Comparative Example 1, the amount of soft monomer added is too much, in Comparative Example 2, no hydroxyethyl methacrylate cross-linking monomer is added, in Comparative Example 3, no anionic emulsifier is added, in Comparative Example 4, no allyloxy nonylphenol propanol polyoxyethylene ether is added, resulting in excessive addition of allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate, in Comparative Example 5, no water-based terpene thickening emulsion is added, in Comparative Example 6, the amount of thickener added is too low, in Comparative Example 7, the drop acceleration is too fast, and in Comparative Example 8, the reaction temperature is too high. The prepared water-based acrylic pressure-sensitive adhesive for battery labels has poor adhesive performance and is easy to warp. Therefore, the water-based acrylic pressure-sensitive adhesive prepared by the raw materials and methods described in this application not only has good initial adhesion, high peeling force, excellent sticking performance, but also has a certain viscosity, and will not warp when used for battery labels.

[0092] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A water-based acrylic pressure-sensitive adhesive for battery labels, characterized in that: The raw materials for its preparation include monomers, initiators, emulsifiers, tackifiers, chain transfer agents, solvents, buffers, and pH regulators; the monomers include soft monomers, hard monomers, and cross-linking monomers; The soft monomer includes one or more of butyl acrylate, n-octyl acrylate, and isooctyl acrylate; The hard monomer includes one or more of styrene, methyl methacrylate, and vinyl acetate; The cross-linking monomer includes one or more of acrylic acid, hydroxyethyl methacrylate, hydroxypropyl methacrylate, N-hydroxymethyl acrylamide, and glycidyl methacrylate; The mass ratio of the soft monomer, the hard monomer and the cross-linking monomer is (45-50): (1-3):

1.

2. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 1, characterized in that: The emulsifier includes a reactive emulsifier and an anionic emulsifier.

3. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 2, characterized in that: The mass ratio of the reactive emulsifier to the anionic emulsifier is 1:(0.5~2).

4. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 2, characterized in that: The reactive emulsifier is allyloxy nonylphenol propanol polyoxyethylene (10) ether ammonium sulfate and allyloxy nonylphenol propanol polyoxyethylene ether.

5. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 2, characterized in that: The anionic emulsifiers are sodium lauryl sulfate and alkylphenol polyoxyethylene ether.

6. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 1, characterized in that: The tackifier is one or more of an aqueous rosin tackifier emulsion and an aqueous terpene tackifier emulsion.

7. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 6, characterized in that: The aqueous rosin tackifying emulsion has a viscosity of 100-400 mPa·s at room temperature, a solid content of 55±2%, and a pH value of 6-8.

8. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 6, characterized in that: The aqueous terpene thickening emulsion has a viscosity of 600-800 mPa·s at room temperature, a solid content of 60±2%, and a pH value of 6-8.

9. The water-based acrylic pressure-sensitive adhesive for battery labels according to claim 1, characterized in that: The added amount of the tackifier is 2% to 3% of the monomer mass.

10. A method for preparing a water-based acrylic pressure-sensitive adhesive for a battery label according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix and stir the emulsifier, monomer, chain transfer agent and deionized water for 1-2 hours to obtain liquid 1; S2, dividing the initiator into initiator 1 and initiator 2, and preparing an initiator 2 solution by mixing initiator 2 and deionized water; S3. The buffer is dissolved in deionized water to prepare a buffer solution. Stir until the buffer is dissolved, raise the temperature to 80-90°C, add initiator 1 and continue stirring until dissolved, and simultaneously drop liquid 1 and initiator 2 solution. The addition should be completed within 3-4 hours. Keep warm at 80-90°C for 1-2 hours, cool to 30-50°C, add viscosity enhancer, continue stirring for 15-30 minutes, add deionized water and pH adjuster to adjust the pH of the system to 6-7, continue stirring for 15-20 minutes, and filter to obtain.

Citation Information

Patent Citations

  • Dual-component emulsion polyacrylate pressure-sensitive adhesive and preparation method and application thereof

    CN105602490A

  • Water-based acrylate pressure sensitive adhesive for battery labels and preparation method thereof

    CN106010379A

  • Medium and high viscosity emulsion type acrylic ester pressure-sensitive adhesive used for protective films, preparation method and application thereof

    CN108285508A

  • High-solid-content peelable water-based pressure-sensitive adhesive and preparation method thereof

    CN113549415A

  • Water-based acrylate pressure-sensitive adhesive and preparation method thereof

    CN113999632A